2018
DOI: 10.1104/pp.18.00832
|View full text |Cite
|
Sign up to set email alerts
|

SNAREs SYP121 and SYP122 Mediate the Secretion of Distinct Cargo Subsets

Abstract: A.M.E.J.).SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins drive vesicle fusion and contribute to homoeostasis, pathogen defense, cell expansion, and growth in plants. In Arabidopsis (Arabidopsis thaliana), two homologous Qa-SNAREs, SYNTAXIN OF PLANTS121 (SYP121) and SYP122, facilitate the majority of secretory traffic to the plasma membrane, and the single mutants are indistinguishable from wild-type plants in the absence of stress, implying a redundancy in their function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…And Sec1/Munc18 proteins interact with some SNARE proteins form the exocyst complex, which initiates membrane fusion [100,101]. Moreover, Waghmare et al [42] found that the membrane traffic mediated by SYP121 and SYP122 is associated differentially with lots of cargo proteins. Xue et al [26] found that VAMP711 regulates ABA-mediated inhibition of PM H+-ATPase activity and drought stress response by regulating stoma closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And Sec1/Munc18 proteins interact with some SNARE proteins form the exocyst complex, which initiates membrane fusion [100,101]. Moreover, Waghmare et al [42] found that the membrane traffic mediated by SYP121 and SYP122 is associated differentially with lots of cargo proteins. Xue et al [26] found that VAMP711 regulates ABA-mediated inhibition of PM H+-ATPase activity and drought stress response by regulating stoma closure.…”
Section: Discussionmentioning
confidence: 99%
“…These clades has diversified into many gene members with evidence of gene duplication in soybean and poplar (Populus trichocarpa).. For example, up to six and three gene copies of SYP122 and SYP124 present in soybean (Glycine max) respectively. Interestingly, the Arabidopsis genes SYP121 and SYP122 as negative regulators of the programmed cell death reaction, the salicylic acid, jasmonic acid and ethylene signalling pathways [41], and the membrane traffic mediated by SYP121 and SYP122 are associated differentially with lots of cargo proteins [42]. The Arabidopsis genes SYP123, SYP124, and SYP125 that function to specify root hair and pollen tissues are specific to this higher taxonomic grouping [43][44][45][46].…”
Section: Phylogenetic Analysis Of Plant Snare Proteinsmentioning
confidence: 99%
“…These genes include AP2C1, a PP2C-type phosphatase that modulates innate immunity (Schweighofer, Kazanaviciute et al, 2007), ACS6, a 1aminocyclopropane-1-carboxylic acid synthase a rate-limiting enzyme that catalyses the committing step of ethylene biosynthesis (Joo, Liu et al, 2008), SYP122, a Qa-SNARE proteins that drive vesicle fusion and are important for cell growth and expansion and pathogen defense (Waghmare, Lileikyte et al, 2018), GER5 an stress-responsive glucosyltransferases, rab-like GTPase activators and myotubularin domain protein involved in ABA-mediated stress responses (Baron, Schroeder et al, 2014), the ethylene response factor ERF022 and the caffeoyl-CoA 3-O-methyltransferase CCOAMT involved in the lignin biosynthesis pathway the accumulation of which induces resistance to aphid feeding (Wang, Sheng et al, 2017).…”
Section: Stress-induced Changes In Methylation Are Associated With Exmentioning
confidence: 99%
“…To explore the possible redundant function of SYP121 and SYP122, Waghmare et al (2018) compared the secreted proteome from wild-type plants to the proteomes of two single mutants, syp121 and syp122. Plants were grown in liquid culture, the secreted proteome was isolated from the growth medium, and specific proteins were identified using mass spectrometry.…”
Section: Spot the Difference: Distinct Cargo-specific Functionality Omentioning
confidence: 99%
“…Further functional characterization of those cargo proteins will contribute to our understanding of the functional differences in the secretion dependent on SYP121 and SYP122. The approach presented by Waghmare et al (2018) exemplifies that it is possible to differentiate between seemingly redundant genes by assessing the single mutants for the phenotype, in this case the secreted proteome, that is most related to the gene function.…”
Section: Spot the Difference: Distinct Cargo-specific Functionality Omentioning
confidence: 99%